Analysis on the Fatty Acids and Volatile Components in Pleurotus geesteranus by HS-SPME-GC-MS - Zhenhua Liang; Shanei Li; Qiongxin Liang; Liqiang Ji; Jinmei Wang; Changqin Li (Journal of Food Quality)
The volatile constituents and fatty acids in Pleurotus geesteranus were assayed by headspace solid-phase microextraction coupled with GC-MS. There were 5 volatile compounds in P. geesteranus that accounted for 43.43% of the total ion current peak area, and its main compounds were 2-undecanone (13.99%), 3-ethyl-2,5-dimethyl pyrazine (12.67%), and l-β-bisabolene (6.79%). Fourteen compounds were identified in the ethanol extract of P. geesteranus and 6 fatty acids were identified from the petroleum ether extract, which accounted for 93.72% and 98.48% of the total ion current peak area, the main compounds in the ethanol extract were ethyl linoleate (67.36%) and ethyl palmitate (21.83%), and the main fatty acids in the petroleum ether extract were linoleic acid (78.22%), palmitic acid (10.74%), and oleic acid (8.13%).